Prognostic value of TNF-α, PCT, IL-8, and HBP, combined with APACHE II score in patients with sepsis - Shuping Guo; Chunyan Liao; Qinghong Liu (Journal of Infection in Developing Countries)
Introduction: This study evaluated the prognostic value of serum cytokines tumor necrosis factor-alpha (TNF-α), procalcitonin (PCT), interleukin-8 (IL-8), and heparin binding protein (HBP); combined with acute physiology and chronic health evaluation II (APACHE II) score in sepsis patients.